Mobile DNA and Sleep Quality - Simon Amez; Floor Denecker; Koen Ponnet; Lieven De Marez; Stijn Baert (Institute of Labor Economics (IZA), 2021)
Previous studies have demonstrated a strong negative association between smartphone use and sleep quality. However, the majority of these studies quantified smartphone use with subjective self-reported metrics. In contrast, the current study contributes to the literature by objectively logging university students' smartphone use and investigating the association thereof with sleep quality. The extensive, nuanced smartphone usage information obtained from this logging also enables us to explore the validity of several mechanisms theorised to underlie the previously reported negative association between smartphone use and sleep quality. In contrast to earlier research, we do not find a significant association between sleep quality and the duration or frequency of students' daily smartphone use. However, students with the internalised habit of launching a greater number of applications per session ('gateway habits') experience worse sleep quality. This finding is consistent with literature showing that smartphone-related stress is more strongly associated with checking habits stemming from 'fear-ofmissing-out' than with overall screen time.
Keywords: I10; L86; 330; mobile DNA; smartphone use; smartphone use logging; fear-of-missing-out; gateway habits; sleep quality